1984
DOI: 10.1037/0022-006x.52.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral and psychodynamic group psychotherapy in treatment of geriatric depression.

Abstract: The purpose of the study was to assess whether depressed geriatric patients would respond to group psychotherapy and, if so, would they respond differently to cognitive-behavioral and psychodynamic group psychotherapy. Thirty-three persons entered the study and 20 completed the 9-month course of treatment. Patients in both types of groups showed statistically and clinically significant reductions on observer-rated measures of depression and anxiety, as well as on self-report measures of depression. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
6

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 20 publications
5
101
0
6
Order By: Relevance
“…* References 20,22,23,25,26,[28][29][30][31][32]39,42,43,45,47,49,[50][51][52][53]56,58,62,[65][66][67]20,[33][34][35][36]47,55,57,59,60,[62][63][64]. …”
Section: Comparisons Using Hdrsmentioning
confidence: 99%
“…* References 20,22,23,25,26,[28][29][30][31][32]39,42,43,45,47,49,[50][51][52][53]56,58,62,[65][66][67]20,[33][34][35][36]47,55,57,59,60,[62][63][64]. …”
Section: Comparisons Using Hdrsmentioning
confidence: 99%
“…7 Punkten Prä-PostUnterschied bei der analytischen Kurztherapie nicht so deut lich ausfiel. Steuer et al (1984) verglichen eine psychodynamisch ausge richtete Gruppentherapie mit einem verhaltenstherapeuti schen Gruppenprogramm an 20 depressiven Geriatriepatien ten. Die Behandlungen erstreckten sich über 9 Monate mit 46 Sitzungen.…”
Section: Ergebnisse Und Erfahrungenunclassified
“…Self-management therapy and education groups were equally effective and superior to wait-list controls in one study (284). CBT and psychodynamic group therapy were more effective than placebo but less effective than tricyclics in other studies (285,286). In a recent study, investigators found that antidepressant medication plus clinical management, either alone or with addition of groupadministered dialectical behavior therapy (skills training and scheduled coaching sessions), found that the medication-dialectical behavior therapy groups had a higher continued remission rate than medications alone (267,287).…”
Section: Psychologicalmentioning
confidence: 99%